VD_FINDINFO Jug / 2013 / 51 vom 5. Februar 2013 - VD Tribunal cantonal (2013)
DÉPENS, CLASSEMENT DE LA PROCÉDURE | 319 al. 1 CPP (CH), 398 al. 2 CPP (CH), 406 al. 1 let. c CPP (CH), 429 al. 1 let. a CPP (CH), 429 CPP (CH), 430 CPP (CH)